Management and the Electronic Computer - Schmidt, Richard N. (Academy of Management Journal, 1960)
Provides a historical background on the use of computers in business. Notion of the failure of computer use in business; Control use of the computer; Implications of the trend in computer use in business as of December 1960 for future managers.